Fabrication of a Novel (PVDF/MWCNT/Polypyrrole) Antifouling High Flux Ultrafiltration Membrane for Crude Oil Wastewater Treatment - Banan Hudaib; Rund Abu-Zurayk; Haneen Waleed; Abed Alqader Ibrahim (Membranes, 2022)
The present work deals with the fabrication of novel poly(vinylidene fluoride) (PVDF)/Multi-wall Carbon Nanotubes (MWCNT)/Polypyrrole (PPy) ultrafiltration membrane by phase inversion technique for the removal of crude oil from refinery wastewater. In situ polymerization of pyrrole with different concentrations of MWCNT ranging from 0.025 wt.% to 0.3 wt.% in PVDF prepared solutions. Measurement of permeability, porosity, contact angle, tensile strength, zeta potential, rejection studies and morphological characterization by scanning electron microscopy (SEM) were conducted. The results showed that membrane with (0.05% MWCNT) concentration had the highest permeability flux (850 LMH/bar), about 17 folds improvement of permeability compared to pristine PVDF membrane. Moreover, membrane rejection of crude oil reached about 99.9%. The excellent performance of this nanocomposite membrane suggests that novel PVDF modification with polypyrrole had a considerable effect on permeability with high potential for use in the treatment of oily wastewater in the refinery industry.